Atherogenesis in rheumatoid arthritis: the “rheumatoidvasculopathy”? - Fietta, P.; Delsante, G. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim: Rheumatoid Arthritis (RA) is associated with accelerated atherogenesis. RA patients have a reduced life expectancy compared to the general population, and cardiovascular (CV) disease (CVD) is recognized as a strong contributor to the excess of morbidity and mortality. Our aim was to review and discuss the recent advances in the knowledge of the RA-associated atherogenesis. Methods: A detailed search of the available literature was performed in the PubMed (U.S. National Library of Medicine) database. Results: Atherosclerosis is an early and common finding in RA patients, positively correlating to the disease duration and severity. Both traditional CV risk factors and disease-related mechanisms may contribute to the RA atherogenesis, however, clinical and epidemiological studies suggest that the systemic inflammation is the major determinant of the RA vascular comorbidity. Patients with RA show an increased risk for CV events compared with the general population, and CVD accounts for nearly 50% of death causes. CV morbidity and mortality strongly correlate with disease activity, whereas the successful pharmacological control of the chronic inflammation decreases the risk of CV complications. Conclusions: Atherogenesis is a precocious feature in RA, as extraarticular manifestation of the syndrome, and might be defined the “rheumatoid vasculopathy”. The better understanding of molecular mechanisms leading to the RA accelerated atherogenesis, the development of effective screening methods, and the identification of successful strategies to control both systemic inflammation and concomitant CV risk factors will allow to minimize the rheumatoid vasculopathy impact on the patients’ morbidity and mortality.